The circular semiosis of Giorgio Prodi - Felice Cimatti (Sign Systems Studies, 2000)
Prodi's semiotics theory comes into being to answer a radical question: if a sign is a cross-reference, what guarantees the relation between the sign and the object to which it is referring? Prodi rebukes all traditional solutions: a subject's voluntary intention, a convention, the iconic relation between sign and object. He refutes the fIrst answer because the notion of intention, upon which it is based, is, indeed, a fully mysterious entity. The conventionalist answer is just as unsatisfactory for it does nothing but extends to a whole group that which cannot be explained for a single component; the iconic one, finally, is rejected toosince in this case the notion of "likeliness", as the basis of the concept of "iconicity", is not explained. Prodi's answer is to locate the model of semiotic relations in the figure of the circle. The circle is life, which is nothing else but an infinite chain of translation and recognition relations amidst ever more complex systems. The circle has neither a beginning nor an end. It has no foundation, no established rule. It holds no cause that cannot become, in turn, effect. Semiosis, then, is based upon life for life, itself, is intrinsically semiotic. We can put the world in signs, that is we can come to know it, because we, ourselves, are a part of that very worldthat through us is made known. Finally, what this implies is that being inside the circle of semiosis-life, an issue arises what is beyond that circle: that is both an aesthetic and a religious problem.